(untitled) (TUTA Journal, 2022)
Attachment theory, originally developed by John Bowlby, has become one of the most influential frameworks in psychology for understanding human relationships. This article traces the evolution of attachment theory, beginning with Bowlby’s emphasis on the biological and evolutionary functions of attachment behaviors and the concept of a secure base. Mary Ainsworth expanded the theory with her groundbreaking Strange Situation Procedure, which identified distinct attachment styles like secure, anxious-ambivalent, avoidant, and later disorganized. Mary Main further advanced the field through her development of the Adult Attachment Interview (AAI), linking early attachment patterns to adult relationships and discovering the phenomenon of disorganized attachment. Contemporary research has integrated insights from neuroscience, emphasizing the role of brain processes and hormones in attachment, while also exploring cross-cultural perspectives and the implications of attachment theory in adulthood, including romantic relationships and mental health. The article highlights the enduring relevance of attachment theory and suggests future research directions, including the influence of technology, neurobiological advances, and cultural diversity. This comprehensive exploration underscores the theory’s lasting impact on psychological research and its practical applications in clinical and social contexts.